Development Characteristics and Sensitivity Analysis of Expansive Soil Slope. (21st July 2022) - Jiang, Pengfei; Kong, Yuanyuan; Song, Zhenyu; Zhao, Ruixin; Zhan, Jiewei; Lin, Xuhui
Abstract : According to laboratory tests of soil samples of Wangyan highway landslide, the mechanism of formation of landslide and the degree of sensitivity of various factors to slope stability are analyzed. It is found that the landslide is destroyed by the properties of expansive soil, the existence of water in the cracks, the loading of artificial filling, and the traction of old landslide. The soil samples were tested for SEM and MIP tests by lyophilization, and the particle morphology, the mode of combination, porosity, and connectivity of the sliding zone soil were observed by a scanning electron microscope. Results show that the sliding zone developed many microfissures and the clay minerals arranged tightly, the pore of size < 0.1 μ m was 60% in undisturbed soil, and the pores of different sizes were distributed uniform in reconstituted soil. The undisturbed soil had typical nonlinear rheological property; The deformation rate of reconstituted was bigger; When the load was 50 kPa and 200 kPa, an expansion phenomena occurred in the sliding zone, which indicated that microstructure could influence the deformation. The strength attenuation of expansive soil slope due to the high content of montmorillonite in the sliding body and the high water content in the cracks are two major factors of the Wangyan highway landslide. Based on the results of previous studies, the a, n, and m values of fitting parameters of Fredlund-Xing soil-water characteristic curve are predicted by using the basic physical properties of soil. It is found that the air intake value and residual suction value of filled soil (loose and broken) and completely weathered sandstone are small, and the water holding capacity in the middle suction range is relatively good. Then, the finite difference software Flac3D was used to build a three-dimensional geological model. The influence of water content, highway load, filling weight, and slope angle on slope stability is considered comprehensively. The order of sensitivity of slope stability about various factors is as follows: water content > slope angle > highway load > filling weight . The results of research can provide a scientific basis for the treatment, protection, and reinforcement of the Wangyan highway landslide.